The Influence of Colonialism on the Existence of the Siantar Kingdom: A Historical and Socio-Political Analysis from Fanon and Gramsci’s Perspectives - Jalatua Habungaran Hasugian (Warisan: Journal of History and Cultural Heritage, 2026)
This study examines the influence of Dutch colonialism on the existence of the Siantar Kingdom in East Sumatra by analysing the dynamics of hegemony, ideological domination, and local resistance. The research examines how colonial power transformed the kingdom's political and social structures and how traditional rulers responded to these interventions. Employing a qualitative historical method through heuristic, source criticism, interpretation, and historiography, this study applies the theoretical perspectives of Frantz Fanon and Antonio Gramsci to interpret colonial practices and anticolonial consciousness. The findings reveal that the Dutch colonial administration strengthened its control by co-opting local elites, institutionalising political authority through the establishment of the Gemeente, and disseminating ideological influence through education and administrative systems. The resistance led by King Sang Naualuh reflected a persistent struggle to defend political sovereignty and cultural identity against colonial domination. This study argues that colonialism in the Siantar Kingdom functioned not only as a form of territorial expansion but also as a structural and ideological mechanism designed to sustain long-term hegemony over indigenous society.